(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Functional gastrointestinal disorders (FGID) are common conditions among children and are characterised by recurring GI symptoms that are not attributable to structural or biochemical abnormalities or as a comorbidity of organic disease. FGID may be caused by various factors, such as disturbances in gut motility, visceral hypersensitivity, mucosal and immune function, gut microbiota, and central nervous system processing. FGID in children lead to a significant symptom burden with associated psychological distress, reduced quality of life, school absenteeism, greater health care expenditure, and missed work for parents. Furthermore, FGID in childhood is also linked to the progression of the disorder into adulthood, such that 25% of children who present with recurrent abdominal pain may subsequently develop irritable bowel syndrome (IBS) as a children. The diagnosis of FGID may be made using the Rome criteria, which are symptom-based guidelines developed using scientific evidence and clinical experience. The most recent iteration is Rome IV, which has paediatric versions available for toddlers (up to four years of age) and children and adolescents (aged four to eighteen years).